2014
DOI: 10.1007/s00572-014-0614-3
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza increase artemisinin accumulation in Artemisia annua by higher expression of key biosynthesis genes via enhanced jasmonic acid levels

Abstract: It is becoming increasingly evident that the formation of arbuscular mycorrhiza (AM) enhances secondary metabolite production in shoots. Despite mounting evidence, relatively little is known about the underlying mechanisms. This study suggests that increase in artemisinin concentration in Artemisia annua colonized by Rhizophagus intraradices is due to altered trichome density as well as transcriptional patterns that are mediated via enhanced jasmonic acid (JA) levels. Mycorrhizal (M) plants had higher JA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 67 publications
4
68
0
Order By: Relevance
“…To further rule out the requirement of JA in maize defense against CLA, Mp708 plants were pretreated with ibuprofen (IBU) or nordihydroguaiaretic acid (NDGA) that blocks the JA pathway, and CLA performance and mir1 expression were monitored before and after CLA infestation. Several studies have shown that the pretreatment of plants with JA inhibitors suppressed the activity of LOX, JA biosynthesis, and/or JA-dependent downstream products (Staswick et al, 1991;Oikawa et al, 2001;Zhang et al, 2009;Mandal et al, 2015). Our results also demonstrate that JA inhibitor treatment significantly suppressed the expression of LOX1 and Proteinase Inhibitor in Mp708 plants and were similar to a level found in the Tx601 maize susceptible inbred line (Supplemental Fig.…”
Section: Rmir1-cp Provides Direct Toxicity To Clasupporting
confidence: 84%
“…To further rule out the requirement of JA in maize defense against CLA, Mp708 plants were pretreated with ibuprofen (IBU) or nordihydroguaiaretic acid (NDGA) that blocks the JA pathway, and CLA performance and mir1 expression were monitored before and after CLA infestation. Several studies have shown that the pretreatment of plants with JA inhibitors suppressed the activity of LOX, JA biosynthesis, and/or JA-dependent downstream products (Staswick et al, 1991;Oikawa et al, 2001;Zhang et al, 2009;Mandal et al, 2015). Our results also demonstrate that JA inhibitor treatment significantly suppressed the expression of LOX1 and Proteinase Inhibitor in Mp708 plants and were similar to a level found in the Tx601 maize susceptible inbred line (Supplemental Fig.…”
Section: Rmir1-cp Provides Direct Toxicity To Clasupporting
confidence: 84%
“…This was followed by a series of reports on the upregulation of DXS transcripts in mycorrhizal roots of various plants (Hans et al, 2004;Strack and Fester, 2006;Floß et al, 2008). Transcription of genes encoding DXS and DXR enzymes is upregulated by AM symbiosis and correlated with quantitative terpenoid concentration in leaves (Mandal et al, 2015a). This increase in transcription and terpenoid content has been ascribed to an increased concentration of the phytohormone jasmonic acid (Mandal et al, 2015a;Nair et al, 2015) and/or improved mineral nutrient availability (Mandal et al, 2015a), and may therefore be influenced by both nutritional and non-nutritional mechanisms (Mandal et al, 2013).…”
Section: Effects Of Arbuscular Mycorrhiza On Terpenoidsmentioning
confidence: 99%
“…Transcription of genes encoding DXS and DXR enzymes is upregulated by AM symbiosis and correlated with quantitative terpenoid concentration in leaves (Mandal et al, 2015a). This increase in transcription and terpenoid content has been ascribed to an increased concentration of the phytohormone jasmonic acid (Mandal et al, 2015a;Nair et al, 2015) and/or improved mineral nutrient availability (Mandal et al, 2015a), and may therefore be influenced by both nutritional and non-nutritional mechanisms (Mandal et al, 2013). Results obtained so far suggest that the AM fungal-mediated increase in concentrations of terpenoids is due to enhanced production of IPP/DMAPP derived from the MEP pathway (Mandal et al, 2015a).…”
Section: Effects Of Arbuscular Mycorrhiza On Terpenoidsmentioning
confidence: 99%
“…Application of two strains of fungi, Glomus macrocarpum and Glomus fasciculatum, to field-grown A. annua also elevates artemisinin yield (Kapoor et al 2007). Colonization of A. annua by Rhizophagus intraradices that forms arbuscular mycorrhiza upregulates the expression of artemisinin biosynthesis genes and also increases artemisinin content (Mandal et al 2014).…”
Section: Abiotic Stress-induced Artemisinin Biosynthesismentioning
confidence: 99%
“…Mycorrhization of A. annua by Rhizophagus intraradices induces allene oxidase synthase gene, which upregulates the expression of artemisinin biosynthesis genes and increase the accumulation of artemisinin. In contrast, the JA biogenesis inhibitor ibuprofen represses the accumulation of artemisinin in both non-mycorrhizal and mycorrhizal plant shoots (Mandal et al 2014). Based on the finding that artemisinin biosynthesis is JA inducible, Yu et al (2012) identified two A. annua JA-responsive transcription factors, AaERF1 and AaERF2, capable of binding to ADS and CYP71AV1 promoters.…”
Section: What Are Transducers Conveying Stress Signals?mentioning
confidence: 99%